1979
DOI: 10.1104/pp.64.2.306
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest Variation in Cellulase, Polygalacturonase, and Pectinmethylesterase in Avocado (Persea americana Mill, cv. Fuerte) Fruits in Relation to Respiration and Ethylene Production

Abstract: Cellulase, polygalacturonase (PG), pectinmethylesterase (PME), respiration, and ethylene production were determined in single "Fuerte" avocado fruits from the day of harvest through the start of fruit breakdown. PME declined from its maximum value at the time of picking to a low level early in the climacteric. PG activity was not detectable in the preclimacteric stage, increased during the climacteric, and continued to increase during the postclimacteric phase to a level three times greater than when the fruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
109
1
3

Year Published

1983
1983
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(125 citation statements)
references
References 15 publications
12
109
1
3
Order By: Relevance
“…Ohtani and Misaki (1983) showed that the seeds of Carica papaya L. exhibited a high level of α-D-galactosidase and α-D-mannosidase activities. Other studies indicated that cellulase activities increase during the maturation of avocados, peaches, strawberries, tomatoes, and papayas (Ignacio et al 2011;Awad and Young 1979;Hobson 1981;Paull and Chen 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Ohtani and Misaki (1983) showed that the seeds of Carica papaya L. exhibited a high level of α-D-galactosidase and α-D-mannosidase activities. Other studies indicated that cellulase activities increase during the maturation of avocados, peaches, strawberries, tomatoes, and papayas (Ignacio et al 2011;Awad and Young 1979;Hobson 1981;Paull and Chen 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Both, PME and PG act in concert to increase cell wall solubilization (Pressey and Avants 1982). De-esterification of cell wall galacturonans by PME may be required prior to hydrolysis by PG (Awad and Young 1979). The activity of these enzymes account for textural changes that collectively contribute to fruit softening, increased pathogen susceptibility and ultimately to the deterioration of fruit tissue (Bennet 2001;Carrillo-López et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…(14) These cell wall structural changes are due to the activities of degrading cellulase enzymes in the cell wall (28,33) and polygalacturonase that result in decreased tissue cohesiveness resulting from the degradation of pectin and cell disarrangement. (34) The mesocarp of an avocado contains common heptoses (C7) sugar, mannoheptulose (35) and its corresponding sugar alcohol, perseitol. (36) A decrease in the C7 sugar content of avocados during ripening has been reported by Bertling and Bower (37) , Liu et al (38) and Meyer and Terry.…”
Section: Fruit Respiration and Ethylene Productionmentioning
confidence: 99%